2020
DOI: 10.1111/1365-2745.13410
|View full text |Cite
|
Sign up to set email alerts
|

Strong self‐regulation and widespread facilitative interactions in phytoplankton communities

Abstract: 1. The persistence of phytoplanktonic diversity in spite of competition for basic resources has long been a source of wonder and inspiration to ecologists. To sort out, among the many coexistence mechanisms suggested by theory and experiments, which ones actually maintain diversity in natural ecosystems, long-term field studies are paramount. 2. We analysed a large dataset of phytoplankton abundance time series using dynamic, multivariate autoregressive (MAR) models. Phytoplankton was counted and identified do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 76 publications
7
11
1
Order By: Relevance
“…We found that the empirical data is indicative of an ecology dominated by competitive and mutalistic interactions, with far fewer predator-prey interactions. This insight is consistent with recent results that suggest that self-regulation (competition) and facilitation (mutualism) are widespread in phytoplankton communities 41 .…”
Section: Discussionsupporting
confidence: 93%
“…We found that the empirical data is indicative of an ecology dominated by competitive and mutalistic interactions, with far fewer predator-prey interactions. This insight is consistent with recent results that suggest that self-regulation (competition) and facilitation (mutualism) are widespread in phytoplankton communities 41 .…”
Section: Discussionsupporting
confidence: 93%
“…through self-limitation and net positive interactions . These results consolidate and expand on findings from primary studies on annual plants (Levine and HilleRisLambers, 2009), perennial plants (Adler, Ellner, et al, 2010;Usinowicz et al, 2012), and phytoplankton Picoche and Barraquand, 2020). Our results show that niche di erences are the main determinant for coexistence across ecological groups, highlighting the importance to sustain mechanisms that promote niche di erences.…”
Section: Large Niche DI Erences Not Small Fitness Di Erences Explained Species Coexistence At a Local Scalesupporting
confidence: 87%
“…Thus, findings that positive interactions can be abundant in nature (Choler et al, 2001;Martorell and Freckleton, 2014;Soliveres et al, 2015;Wainwright et al, 2016;Picoche and Barraquand, 2020) do not contradict our result that net facilitation was only frequently observed in perennial plants and phytoplankton.…”
Section: Erences and Similarities Among DI Erent Ecological Groupssupporting
confidence: 64%
See 1 more Smart Citation
“…Further, co-occurrence patterns are scale dependent and regional analyses are not suited to assessing local-scale species interactions (König et al, 2021). Recognizing a need to directly estimate species interaction coefficients, recent work has expanded multivariate autoregressive models for use in more diverse communities (Picoche & Barraquand, 2020), including examining which linear combinations of species abundances best predict future growth rates (Ovaskainen et al, 2017a). This approach is effective for binning species based on their competitive effects, but does not account for variation in the environment.…”
Section: Introductionmentioning
confidence: 99%